Behavior Changes in Paulo Coelho Veronika Decides to Die: A Psychological Approach - Prakoso, Bagas Suryo; Daulay, Resneri (NOTION: Journal of Linguistics, Literature, and Culture, 2020)
This research entitled â€œBehavior Changes in Paulo Coelhoâ€™s Veronika Decides to Die: A Psychological Approachâ€. The purpose of this study is to analyze the personality of the main character presented in the novel. In addition, the aim of this research is to reveal the main characterâ€™s environments contribute to the characterâ€™s motivation to life. This novel conducted the struggle from Veronika as the main character for finding her motivation to life.This study used qualitative research; descriptive qualitative methods are used to analyze data. This study used three main concepts of social cognitive theory by Albert Bandura (1986), there are reciprocal determinism, therapy, and dysfunction behavior/depression. This study also applied the theory of social cognitive theory in the book entitled The Theory of Personality by Jess Feist as a tool to analyze the personality of the main character also the main characterâ€™s environments contribute to the characterâ€™s motivation to life in the novel Veronika Decides to Die by Paulo Coelho.In this study, the researcher found two main results. First, this study indicated personality of Veronika as the main character in the novel Veronika Decides to Die based on the social cognitive theory concept that is dysfunction behavior. Based on concept of dysfunction behavior, it shows that Veronika is an introvert person, fainthearted, and suffering from depression. Second, this study discovered the main characterâ€™s environments contribute to the characterâ€™s motivation to life based on the social cognitive concepts, they are reciprocal determinism and therapy. Based on that theoretical concept, it shows that Veronikaâ€™s environment really helps her to find her motivation to life. They are Mari, Zedka, and Edward.Keyword: Motivation to life, Dysfunction Behavior, Reciprocal Determinism and Therapy